Normative Aspects of Publishing Activity of European Scientific Libraries (case of the National Libraries of the Baltic Countries) - Dubas Tetiana (Наукові праці Національної бібліотеки України імені В.І. Вернадського)

(untitled)
The article examines the peculiarities of the process of normalization of publishing activity of the national libraries on the example of Estonia, Latvia, and Lithuania. The objects of the research - national libraries - are located in different countries of Europe, but are focused on solving common tasks of information service and ensuring high quality of library and information services, publishing products. The Baltic countries national libraries carry out library and scientific publishing activities and ensure the implementation of the national information policy, which is within their competence. The purpose of the article is to high light the experience of Baltic countries national libraries in publishing activity from the stand point of its normalization. The research methodology is based on the analysis and synthesis of information obtained as a result of the study of the problem of normative approaches to the publishing activity of the Baltic countries national libraries. A traditional review of the existing source base and regulatory documents is also involved. Emphasis is placed on the importance of applying regulatory documents that define modern requirements for library products. The importance of standardization in the publishing activities of the national library is emphasized. Conclusions. The experience of the Baltic countries national libraries shows the intensive development of their publishing activity, which is represented by a variety of scientific products (both printed and electronic) and the provision of support for publishing activity with an appropriate regulatory and legal framework, with the aim of streng thening the functions and role of librariesin the modern world, improving the efficiency of library products.